2022
DOI: 10.1093/mr/roac064
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms compatible with Rome IV functional bowel disorder in patients with ankylosing spondylitis

Abstract: Objectives To determine the frequency of symptoms meeting Rome IV functional bowel disorder (FBD) in patients with ankylosing spondylitis (AS), investigate factors associated with FBD symptoms, and assess whether having FBD symptoms might influence AS disease activity. Methods In this cross-sectional study, we enrolled 153 AS patients without known colonic ulcer and 56 sex- and age-matched controls to evaluate FBD (or its sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Therefore, exploring the molecular mechanisms between AS and IBD, early identification, and intervention undoubtedly have important clinical significance. According to earlier research, AS and IBD own have their unique genetic inheritance [ 27 , 28 ], and the activity of the two diseases affects one another [ 29 , 30 ]. As a result, scientists focus primarily on genetics to investigate the comorbidity mechanism of the two illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, exploring the molecular mechanisms between AS and IBD, early identification, and intervention undoubtedly have important clinical significance. According to earlier research, AS and IBD own have their unique genetic inheritance [ 27 , 28 ], and the activity of the two diseases affects one another [ 29 , 30 ]. As a result, scientists focus primarily on genetics to investigate the comorbidity mechanism of the two illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…The smart phone Spondyloarthritis Management System (SpAMS) application was used to document the assessment of AS [ 18 ], including the Ankylosing Spondylitis Disease Activity Score based on C-reactive protein (ASDAS-CRP), the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), the Assessment of the Spondyloarthritis International Society Health Index (ASAS HI), the Bath Ankylosing Spondylitis Functional Index (BASFI), and the Bath Ankylosing Spondylitis Metrology Index (BASMI) [ 19 , 20 , 21 , 22 , 23 ]. Gut problems, including abdominal pain, constipation, diarrhea, and bloating had been investigated and reported previously [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have suggested that improvement in FBD symptoms, particularly chronic diarrhea, may positively impact the disease state of individuals diagnosed with AS. This raises the possibility that addressing FBD symptoms may play a role in managing the overall condition of individuals with AS [ 6 ].…”
Section: Introductionmentioning
confidence: 99%